2020
DOI: 10.36555/almana.v4i2.1417
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Training and Career Development on Employee Job Satisfaction

Abstract: A high target has always been the orientation of almost all companies because it will make the company progress and develop, so the company must create employee job satisfaction so that the employee can work optimally and accelerate what is the company's orientation. Career Training and Development is an important factor of course within the company because it is a motivating factor for employees to be able to make the company progress and develop. This research aims to assist PT Kartika Inti Sejati in realizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Considering the training investment and return in terms of satisfaction, Price and Reichert (2017) identified that continuous investment on learning and education of nurses enhance their career growth opportunities and ensure job satisfaction. Study also showed that there is a significant association between training investment for career growth opportunities and employee satisfaction while considering remaining factors constant (Mulyadi, 2020). Dipietro (2006) Training equips an individual with the expertise needed to perform their assigned jobs.…”
Section: Relations Between Training Investment and Job Satisfactionmentioning
confidence: 98%
“…Considering the training investment and return in terms of satisfaction, Price and Reichert (2017) identified that continuous investment on learning and education of nurses enhance their career growth opportunities and ensure job satisfaction. Study also showed that there is a significant association between training investment for career growth opportunities and employee satisfaction while considering remaining factors constant (Mulyadi, 2020). Dipietro (2006) Training equips an individual with the expertise needed to perform their assigned jobs.…”
Section: Relations Between Training Investment and Job Satisfactionmentioning
confidence: 98%
“…Banyak faktor yang mempengaruhi kinerja karyawan termasuk keselamatan kesehatan kerja, pelatihan dan pengembangan karir [5]. Keselamatan kesehatan kerja adalah variabel yang dapat memberikan ketenangan bagi karyawan dalam melaksanakan pekerjaannya, apalagi jika pekerjaan yang dilakukan karyawan itu berisiko [6]. Keselamatan kesehatan kerja menunjuk kepada kondisi-kondisi fisiologis-fisikal dan psikologis tenaga kerja yang diakibatkan oleh lingkungan kerja yang disediakan oleh perusahaan [7].…”
Section: Pendahuluanunclassified
“…Career development policies, such as training, mentoring, and skill diversification initiatives, are essential for shaping employees' professional growth and improving their performance [14]- [16]. These policies provide employees with opportunities to acquire new skills, expand their knowledge, and develop their careers within the organization [17], [18]. Intrinsic and extrinsic factors, such as work motivation, play an important role in driving employee performance.…”
Section: Introductionmentioning
confidence: 99%